Spatial policy in cities during the Covid-19 pandemic in Poland - Śleszyński, Przemysław; Nowak, Maciej; Blaszke, Małgorzata (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The ‘geographic’ aim of the study is to find the regularity of the increase in the number of infections in larger cities and their surroundings. The goal related to the science of public policy is to determine the implemented and potential effects related to spatial policy in Polish cities. The geographic part of this publication uses the available data on the development of the number of identified (recorded) infections. The part of the paper related to the accomplishment of the goal covering the sphere of public policy is primarily of an overview nature. It contains the characteristics of the spatial management system in Poland (including tools affecting the broadest impact on urban space) and the introduced and potential changes caused by the pandemic.